Megahertz‐rate ultrafast X‐ray scattering and holographic imaging at the European XFEL. (30th September 2022) - Zhou Hagström, Nanna; Schneider, Michael; Kerber, Nico; Yaroslavtsev, Alexander; Burgos Parra, Erick; Beg, Marijan; Lang, Martin; Günther, Christian M.; Seng, Boris; Kammerbauer, Fabian; Popescu, Horia; Pancaldi, Matteo; et al.
Abstract : Results from the first megahertz‐repetition‐rate X‐ray scattering experiments at the Spectroscopy and Coherent Scattering (SCS) instrument of the European XFEL are presented. Abstract : The advent of X‐ray free‐electron lasers (XFELs) has revolutionized fundamental science, from atomic to condensed matter physics, from chemistry to biology, giving researchers access to X‐rays with unprecedented brightness, coherence and pulse duration. All XFEL facilities built until recently provided X‐ray pulses at a relatively low repetition rate, with limited data statistics. Here, results from the first megahertz‐repetition‐rate X‐ray scattering experiments at the Spectroscopy and Coherent Scattering (SCS) instrument of the European XFEL are presented. The experimental capabilities that the SCS instrument offers, resulting from the operation at megahertz repetition rates and the availability of the novel DSSC 2D imaging detector, are illustrated. Time‐resolved magnetic X‐ray scattering and holographic imaging experiments in solid state samples were chosen as representative, providing an ideal test‐bed for operation at megahertz rates. Our results are relevant and applicable to any other non‐destructive XFEL experiments in the soft X‐ray range.